Pneumonia associated with mechanical ventilation and preventive nursing care: literature review - Silva , Lisianne Natália Santos (2022)
Ventilator-associated pneumonia (VAP) is defined as a pulmonary infection that appears between 48 to 72 hours after endotracheal intubation and initiation of invasive mechanical ventilation (IMV), and is one of the most fearful complications of intensive care. The study's general objective is to analyze nursing actions in the prevention of ventilator-associated pneumonia. This is an integrative, descriptive and exploratory literature review, in which the following guiding question was used “Which nursing actions contribute to the prevention of ventilator-associated pneumonia?”, applied to the PICO strategy and using Boolean “AND” in Bireme, Cinahl and Pubmed databases via Medline. Altogether 12 articles were selected according to the previously established criteria, most of the studies addressed the level of knowledge of nursing professionals regarding preventive measures in pneumonia associated with mechanical ventilation, in addition to the professionals' adherence to preventive actions and the use of strategies that can be applied in daily clinical practice. It is clear that the care provided must be focused both on the illness process that the patient experiences and on the prevention of other pathologies, such as pneumonia, which can generate several complications and even lead to death.